How optimal caseload midwifery can modify predictors for preterm birth in young women: Integrated findings from a mixed methods study. (October 2016) - Allen, J.; Kildea, S.; Stapleton, H.
Abstract: Objective: to identify possible mechanisms by which caseload midwifery reduces preterm birth for young childbearing women. Design: a mixed methods triangulation, convergence design was used to answer the research question 'How does the way maternity care is provided affect the health and well-being of young women and their babies?' The project generated quantitative and qualitative findings which were collected and analysed concurrently then separately analysed and published. The research design enabled integration of the quantitative and qualitative findings for further interpretation through a critical pragmatic lens. Setting: a tertiary maternity hospital in Australia providing care to approximately 500 pregnant young women (aged 21 years or less) each year. Three distinct models of care were offered: caseload midwifery, young women's clinic, and standard 'fragmented' care. Participants: a cohort study included data from 1971 young women and babies during 2008–2012. An ethnographic study included analysis of focus group interviews with four caseload midwives in the young women's midwifery group practice; as well as ten pregnant and postnatal young women receiving caseload midwifery care. Findings: integrated analysis of the quantitative and qualitative findings suggested particular features in the model of care which facilitated young women turning up for antenatal care (at an earlier gestation and more frequently) and buying in to the process (disclosing risks, engaging in self-care activities and accepting referrals for assistance). We conceptualised that Optimal Caseload Midwifery promotes Synergistic Health Engagement between midwife and the young woman. Key conclusions: optimal Caseload Midwifery (which includes midwives with specific personal attributes and philosophical commitments, along with appropriate institutional infrastructure and support) facilitates midwives and young clients to develop trusting relationships and engage in maternity care. Health engagement can modify predictors for preterm birth that are common amongst pregnant adolescents by promoting earlier maternity booking, sufficient antenatal care, greater emotional resilience, ideal gestational weight gain, less smoking/drug use, and fewer untreated genito-urinary infections. Implications for practice: the institutional infrastructure and managerial support for caseload midwifery should value and prioritise the philosophical commitments and personal attributes required to optimise the model. Furthermore the location of visits, between appointment access to primary midwife, and back-up system should be organised to optimise the midwife-woman relationship in order to promote the young woman's engagement with maternity care. Highlights: The mechanism by which caseload midwifery reduces preterm birth is unclear. Results of this mixed methods study suggests 'optimal' caseload midwifery promotes young women to engage in maternity care. 'Synergistic health engagement' involves 'turning up' and 'buying in'. 'Synergistic health engagement' can modify predictors for preterm birth in young women.